Morocco protest movements in the post-constitutional reform - Ibnu Burdah (Indonesian Journal of Islam and Muslim Societies, 2017)
dth: 0px; " The research describes and explains the wave of protest movement in theKingdom of Morocco, one of the Muslim countries in the Western Arab, in the post-2011 constitutional referendum. The constitutional reform was carried out as a response to the large and massive people protest. Unlike the cases in other neighboring states where “Arab Spring” took place, the Moroccan movement receded without neither the fall of the regime nor massive casualties. However, intense protest kept taking place, especially in Muhammad V Street leading to the Parliament Building. Some interesting questions arise, including what the nature of the current protest is and why people still protest after the vast popular agreement toward the constitutional referendum. Based on library research and intense observation for forty days, and interviews, this study found that, to some extent, the Morocco protest has the same nature as that of the Arab Spring. The protest has “hidden agendas” although there are evidences that they dissembled in “smaller and partial issues because of some reasons”. The author holds that Morocco is an important lesson for political reform in the current turbulent Arab world and, to abroader context, in the Muslim world. 0px; " Penelitian ini mendeskripsikan dan menjelaskan gerakan protest di KerajaanMaroko, salah satu negara Muslim di Arab Barat, paska referendum konstitusitahun 2011. Reformasi konstitusional di Maroko telah dilaksanakan sebagai respon terhadap protes rakyat dalam skala luas dan massif. Berbeda dengan yang terjadi di negara-negara “Musim Semi Arab” yang lain, gerakan protes itu surut tanpa disertai jatuhnya rezim dan jatuhnya korban dalam jumlah yang besar. Namun, Maroko masih diwarnai gerakan protes yang cukup intensif hampir setiap hari (kendati skalanya lebih kecil) khususnya di Jalan Muhammad V sampai depan gedung parlemen. Pertanyaannya adalah apa sesungguhnya karakter dari protes-protes yang masih berlangsung bahkan hingga saat ini? Mengapa mereka masih melakukan protes pasca persetujuan secara luas rakyat Maroko terhadap reformasi konstitusi? Penelitian yang dilakukan dengan cara studi kepustakaan yang didukung oleh observasi di lapangan sekitar 40 hari, berkesimpulan bahwa karakter protes itu adalah “Arab Springs” (mengarah pada penjatuhan rezim) kendati itu tak dinyatakan secara terbuka. Mereka memiliki agenda terselubung itu dan tidak mengemukakannya dengan berbagai alasan. Penulis berpendapat, Maroko adalah pelajaran penting bagi reformasi politik di dunia Arab yang sedang bergolak saat ini, bahkan mungkin pula untuk dunia Islam.